Nursing Perspectives: Reflecting History and Informal Coercion in De-escalation Strategies - Rabenschlag, Franziska; Cassidy, Christoph; Steinauer, Regine (Frontiers in Psychiatry, 2019)
Health professionals like nurses respond to aggression and violence with de-escalation techniques, and still often with coercive measures. Such measures applied by institutions are often rooted in historically grown traditions rather than evidence, reflection, or formation. In this article, we present de-escalation strategies integrating a high and critical awareness toward traditions and the practice of formal and informal coercion.